If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x-4)=18-2(3-4x)
We move all terms to the left:
4(3x-4)-(18-2(3-4x))=0
We add all the numbers together, and all the variables
4(3x-4)-(18-2(-4x+3))=0
We multiply parentheses
12x-(18-2(-4x+3))-16=0
We calculate terms in parentheses: -(18-2(-4x+3)), so:We get rid of parentheses
18-2(-4x+3)
determiningTheFunctionDomain -2(-4x+3)+18
We multiply parentheses
8x-6+18
We add all the numbers together, and all the variables
8x+12
Back to the equation:
-(8x+12)
12x-8x-12-16=0
We add all the numbers together, and all the variables
4x-28=0
We move all terms containing x to the left, all other terms to the right
4x=28
x=28/4
x=7
| 12s-11s=17 | | 10g+10g=20 | | -4c-1=2c-19 | | 540=b+3/2b+90+b+45+2b-90 | | 2n-1/3n=24 | | -15s+7=-18s+13+9s | | 26.17=5g+3.77 | | 8n-8n+4n-2n-n=14 | | 10g-(2(g+9)+50=0 | | -1-6j=-7j+6 | | -p+9=-2p | | 8k-2=-10+9k | | P-p+2p-p=1 | | g+3+6g=6g-7 | | 615=5x-^3 | | 2t=-8+3t | | -1/2y-1/2y+5/6y=-2/3 | | 10+m=-10+3m | | 28=y÷2 | | 4x+3(4x44)=44 | | -8-3u+5u=10-4u | | -9-7y=-8y | | 2(x+1)−5(x−3)=5 | | -10+3j=10j+4 | | x-6/x-2=x+5/x+4+1 | | 2.5(x-5)=-x-9 | | -6u+6=-8u | | -7-7s=9-5s | | 2(-10s+5)=-5s+40 | | 9-9y=-8y | | -v=-3v+10 | | 3n-3n+10=5n-3n |